Improving Organizational Citizenship Behavior In The Era Of Independent Learning - Sri Setyaningsih; Herfina Herfina; Triningsih Triningsih (Universitas Pakuan, 2023)
This study aims to analyze the improvement of Organizational Citizenship Behavior (OCB) among elementary school teachers within the context of Indonesia’s Independent Learning (Merdeka Belajar) policy by examining the roles of transformational leadership and self-efficacy. Using a quantitative research design with a path analysis approach, data were collected from 173 certified civil servant teachers in accredited “A” public elementary schools across Depok City, West Java, through proportional random sampling and structured questionnaires. The data were analyzed using descriptive and inferential statistics with SPSS 22 to test the hypothesized relationships among variables. The results show that transformational leadership has a significant positive effect on OCB (sig = 0.107 α = 0.05), while self-efficacy does not show a significant influence (sig = 0.884 α = 0.05). These findings indicate that school principals’ visionary and inspirational leadership behaviors enhance teachers’ willingness to engage in voluntary and collaborative actions beyond formal job requirements, a critical factor for advancing educational quality in the Independent Learning era. The study concludes that strengthening transformational leadership practices and cultivating teachers’ professional self-efficacy through continuous training and supportive work environments are essential strategies to sustain a high level of OCB and foster a positive, innovative school culture.